The forms of objectivity: A connection between Lukács and early Critical Theory - López Álvarez, Pablo (Analysis. Journal of Philosophical Research, 2023)
The theoretical significance of G. Lukács is not limited to his place in what is known as Western Marxism. His philosophical work up to History and Class Consciousness (1923) offers unique insights into the evolution of modern social forms, the possibility of their aesthetic and epistemological apprehension, and modes of individual and collective action. The reception of his work in the thinkers of early Critical Theory (Adorno and Benjamin) allows for a broader discussion of ways of interpreting the reified world and transforming it. The focus on the problems of objectification, reification and second nature has implications for a contemporary social ontology and theory of experience.